5-hydroxytryptamine and sexual behaviour in rhesus monkeys - Gradwell, Peter Bertram (Rhodes University, Faculty of Humanities, Department of Psychology, 1976)
Selective inhibition of 5-hydroxytryptamine by parachlorophenylalanine (PCPA) is able to restore sexual receptivity in female rhesus monkeys made unreceptive by bilateral adrenalectomy. PCPA in the doses used reduces the levels of 5-hydroxyindoleacetic acid (5HIAA) in the cerebrospinal fluid to 40 per cent of the normal oestradioltreated condition. Both the increased sexual receptivity and the lowered 5HIAA levels "in the CSF are in turn reversed by 5-hydroxytryptophal (5HTP), the irrmediate precursor of 5HT and the substance whose synthesis is inhibited by PCPA. 5HTP on its own reduces sexual receptivity and increases 5HIAA levels in the CSF of ovariectomised, oestradiol-treated (but otherwise intact) female rhesus monkeys. A substance other than an adrenal androgen has therefore been shown to restore sexual receptivity in adrenalectomised female monkeys . Testosterone propionate and oestradiol benzoate both lower the turnover rates of 5HT in the brains of ovariectomised female monkeys, as measured by the 2 hour probenecid test. Taken together, these findings suggest that adrenal androgens could act on specific sites in the female monkey brain via 5HT-containing neural systems, to control (or at least influence) sexual receptivity. All the results of administering oestradiol to ovariectomised monkeys in these experiments are consistent with the established roles of this hormone in female sexual attractiveness and in the gonadotrophin- controlling systems of the hypothalamo-hypophyseal axis. In contrast to these findings on 5HT and sexual receptivity in female monkeys, no clear role for 5HT- containing neural systems could be demonstrated in the grooming, aggressive or social behaviours of female monkeys. No clear role for 5HT could be demonstrated in the refractory period following ejaculation in male monkeys , or when testosterone replacement is given to castrated male monkeys.
Keywords: Rhesus monkey -- Behavior; Sexual behavior in animals